2018
DOI: 10.1016/j.celrep.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

PHLDA1 Mediates Drug Resistance in Receptor Tyrosine Kinase-Driven Cancer

Abstract: SummaryDevelopment of resistance causes failure of drugs targeting receptor tyrosine kinase (RTK) networks and represents a critical challenge for precision medicine. Here, we show that PHLDA1 downregulation is critical to acquisition and maintenance of drug resistance in RTK-driven cancer. Using fibroblast growth factor receptor (FGFR) inhibition in endometrial cancer cells, we identify an Akt-driven compensatory mechanism underpinned by downregulation of PHLDA1. We demonstrate broad clinical relevance of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 57 publications
(75 reference statements)
3
42
1
6
Order By: Relevance
“…Reduced expression of PHLDA1 has been reported in melanoma, breast carcinoma, oral carcinoma, and gastric adenocarcinoma, and lower expression of PHLDA1 is associated with the malignant phenotype of cholangiocarcinoma . It has also been reported that PHLDA1 is involved in the repression of growth factor signaling . Although these reports suggest that PHLDA1 can function as a tumor suppressor, its precise molecular activity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced expression of PHLDA1 has been reported in melanoma, breast carcinoma, oral carcinoma, and gastric adenocarcinoma, and lower expression of PHLDA1 is associated with the malignant phenotype of cholangiocarcinoma . It has also been reported that PHLDA1 is involved in the repression of growth factor signaling . Although these reports suggest that PHLDA1 can function as a tumor suppressor, its precise molecular activity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] It has also been reported that PHLDA1 is involved in the repression of growth factor signaling. 19,20 Although these reports suggest that PHLDA1 can function as a tumor suppressor, its precise molecular activity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A capacidade dos domínios PHL de se ancorar transitoriamente na superfície da membrana intracelular e participar de múltiplos processos de transdução de sinais, têm sido alvo de muitos estudos (JIANG et al, 2015;SCHEFFZEK;WELTI, 2012). Alguns trabalhos tem demonstrado que proteínas com o domínio funcional PHL podem suprimir a atividade de AKT (serine/threonine kinase 1) pela interferência direta na ligação desta oncoproteína aos fosfotidilinositol, inibindo sua fosforilação e, consequentemente, ativação de vias de proliferação e sobrevivência celular (DAI et al, 2012;FEARON et al, 2018;KAWASE et al, 2009). A desregulação da via AKT tem sido implicada em uma variedade de canceres humanos e a identificação de potenciais inibidores desta via tem sido considerado uma estratégia promissora para tratamentos anti-câncer (PARIKH et al, 2012; SHARIATI; MERIC-BERNSTAM, 2019).…”
Section: Membros Da Família Phlda (Pleckstrin Homology-like Domain Faunclassified
“…Agentes indutores de estresse celular, como aqueles provocados pelo choque térmico, estresse oxidativo e estresse do retículo endoplasmático, são capazes de induzir a expressão de PHLDA1 em diferentes tipos celulares (HAYASHIDA et al, 2006;HOSSAIN et al, 2003;JANUS et al, 2020;JOO et al, 2007;PARK et al, 2013), podendo levar a mudanças morfológicas, diminuição de adesão celular e promoção de anoikis, e que ainda sua expressão pode ser regulada positivamente por IGF-1 (insulin-like growth factors 1) (TOYOSHIMA et al, 2004;WU et al, 2010), pela via ERK (extracellular-signal-regulated kinase) (LYU et al, 2016;OBERST et al, 2008), pela quinase HER2 (FEARON et al, 2018;LI et al, 2014a;MAGI et al, 2018), pelo estrogênio via ER (KASTRATI; CANESTRARI; FRASOR, 2015; MARCHIORI; CASOLARI; NAGAI, 2008) e por p53 (CHEN et al, 2018). O PHLDA1 tem sido reportado por inibir síntese de certas proteínas e possivelmente exerce um papel na tradução proteica (HINZ et al, 2001;OBERG et al, 2004).…”
Section: Phlda1: Papel Biológico E Relação Com O Câncer De Mamaunclassified
See 1 more Smart Citation